Mitofusin-2: A New Mediator of Pathological Cell Proliferation - Xin, Yanguo; Li, Junli; Wu, Wenchao; Liu, Xiaojing (Frontiers in Cell and Developmental Biology, 2021)
Cell proliferation is an important cellular process for physiological tissue homeostasis and remodeling. The mechanisms of cell proliferation in response to pathological stresses are not fully understood. Mitochondria are highly dynamic organelles, whose shape, number and biological functions are modulated by mitochondrial dynamics, including fusion and fission. Mitofusin-2 (Mfn-2) is an essential GTPase-related mitochondrial dynamics protein for maintaining mitochondrial network and bioenergetics. A growing body of evidence indicate that Mfn-2 has a potential role in regulating cell proliferation in various cell types. Here, we review these new functions of Mfn-2, highlighting its crucial role in several signaling pathways during the process of pathological cell proliferation. We conclude that Mfn-2 could be a new mediator of pathological cell proliferation and a potential therapeutic target.